Exploring the physicochemical profile and the binding patterns of selected novel anticancer Himalayan plant derived active compounds with macromolecular targets - Arun Bahadur Gurung; Atanu Bhattacharjee; Mohammad Ajmal Ali (Informatics in Medicine Unlocked, 2016)
Plants are vital source of compounds offering plethora of therapeutic effects against various ailments without much side effects. Due to wide spread prevalence and drug resistance in cancer; there is an urgent need for discovery of new anti-cancer drugs. In the present study, selected novel anti-cancer plants derived compounds (cmpd1 to cmpd15) from Himalayan region were docked with defined molecular targets that regulate cell proliferation and apoptosis. The binding energies of best docked compounds ranged between â8.0Â kcal/mol and â11.71Â kcal/mol. Further analysis revealed critical hydrogen bonds and hydrophobic interactions between compounds and targets. The best docked compounds viz., cmpd15 against cyclin-dependent kinase-2 (CDK-2), cmpd8 against CDK-6 and cmpd9 against Topoisomerase I and II showed higher binding affinities than the native co-crystal ligands. The root mean square deviation (RMSD) and potential energy plot clearly indicates the stability of the complexes during 20Â ns molecular dynamics (MD) simulation. The Molecular Mechanics/Poisson Boltzmann Surface Area (MM/PBSA) binding energy analysis revealed Van der Waals energy component which is the principal stabilizing energy for their interactions except CDK-2/cmpd15 complex. The polar solvation energy did not have favorable contribution to their stabilization. The binding energy decomposition analysis revealed per residue contribution for each docked complexes. Physicochemical profile studies showed that majority of the compounds conform to Lipinski's rule of five (ROF) having low to high blood brain barrier (BBB) penetration, human intestinal absorption, plasma binding protein inhibition and P glycoprotein inhibition. Keywords: ADMET, Anticancer, MM/PBSA, Molecular docking, Molecular dynamics simulation and plant derived compounds